FINANCIAL DISTRESS, AUDIT COMMITTEE, INDEPENDENT COMMISSIONER, AND AUDIT QUALITY'S IMPACT ON BANKING TAX AVOIDANCE - Kurniawati, Herni; Jap, Yustina Peniyanti (International Journal of Application on Economics and Business, 2025)
Since both tax avoidance and tax planning use legal means to lower or eliminate tax obligations, tax avoidance is defined as a tax reduction activity. It can range from profitable tax investments (like tax-exempt communal bonds) to aggressive strategies that might not be defended if challenged. In reality, tax evasion is a complicated issue as, while it does not violate any laws, the government opposes tax collectors having the authority to control taxes. As a result, studies on tax evasion across a range of corporate industries and nations yield varying conclusions. The aim of this study is to provide empirical evidence regarding the effects of Independent Commissioners, Audit Committees, and Audit Quality on tax avoidance actions taken by public bank managers. The research methodology is quantitative description utilizing annual report data, and the research sample is the banking industry during the period 2019–2022. The Eviews 12 software program is utilized to support this research. The study's findings demonstrate that financial distress, audit quality, and independent commissioners can all reduce the amount of tax avoidance behavior carried out by banking management. However, the number of audit committees owned by banks cannot both increase or decrease the tax avoidance behavior of banking management. With the goal of lowering potential tax avoidance behavior by management, the contribution to this study gives stakeholders—including shareholders and the government (Directorate General of Taxes)—insight into the significance of the board of commissioners' and audit committee's roles, audit quality, and the financial difficulties that banks face.